2023
DOI: 10.1111/gcb.16670
|View full text |Cite
|
Sign up to set email alerts
|

Potential aboveground biomass increase in Brazilian Atlantic Forest fragments with climate change

Abstract: Fragmented tropical forest landscapes preserve much of the remaining biodiversity and carbon stocks. Climate change is expected to intensify droughts and increase fire hazard and fire intensities, thereby causing habitat deterioration, and losses of biodiversity and carbon stock losses. Understanding the trajectories that these landscapes may follow under increased climate pressure is imperative for establishing strategies for conservation of biodiversity and ecosystem services. Here, we used a quantitative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 120 publications
0
8
0
Order By: Relevance
“…Another important point is the need for not only preserve forests in lower fragmentation class, but also those in higher fragmentation classes to increase the resilience of AF functions to climate change. A recent model predicting the impact of climate change on AF above-ground biomass (AGB) showed that the most significant loss of AGB, up to 40%, compared to the baseline value, is likely to occur between latitudes 13 • and 20 • south (Ferreira et al 2023). Our results showed deforestation and degradation leading to core area loss in southern and south-eastern forests at these latitudes, which may decrease the capacity of forests to counteract the effects of changes in climate.…”
Section: Fragmentation Impact On Atlantic Forest Carbon Balancementioning
confidence: 58%
“…Another important point is the need for not only preserve forests in lower fragmentation class, but also those in higher fragmentation classes to increase the resilience of AF functions to climate change. A recent model predicting the impact of climate change on AF above-ground biomass (AGB) showed that the most significant loss of AGB, up to 40%, compared to the baseline value, is likely to occur between latitudes 13 • and 20 • south (Ferreira et al 2023). Our results showed deforestation and degradation leading to core area loss in southern and south-eastern forests at these latitudes, which may decrease the capacity of forests to counteract the effects of changes in climate.…”
Section: Fragmentation Impact On Atlantic Forest Carbon Balancementioning
confidence: 58%
“…The algorithm has been commonly used for species distribution and habitat modeling, and it is based on the probabilistic inference method to estimate the maximum entropy distribution from incomplete datasets (Phillips et al, 2006(Phillips et al, , 2017. The method has been successfully applied to estimate the occurrence of fires in the landscape (Parisien and Moritz, 2009;Fonseca et al, 2016) and the aboveground biomass distribution (Saatchi et al, 2011;Ferreira et al, 2023).…”
Section: Data Analysis and Model Calibrationmentioning
confidence: 99%
“…This study found that the contribution of precipitation seasonality and precipitation of the warmest quarter, related to moisture, exceeded that of temperature-related parameters in the model. In addition, the spatial variation in above-ground biomass driven by climate change is unclear, and the MaxEnt model is an important approach to exploring this issue [32].…”
Section: Accuracy and Uncertainty Analysis Of Agb Estimationmentioning
confidence: 99%
“…While few applications of the MaxEnt model for estimating biomass have been made to date, notable examples include the work of Saatchi et al [27], who applied the model to estimate forest biomass in Latin America, South Africa, and Southeast Asia, obtaining an overall mean uncertainty of ±30% for AGB at the pixel scale. Since then, scholars have made further applications in regions such as Mexico [28], the Congo [29], the United States [30,31], and the Brazilian Atlantic Forest [32]. However, the established MaxEnt model for biomass estimation has largely been applied at large scales, such as intercontinental and national scales, with limited applications to small-scale regions.…”
Section: Introductionmentioning
confidence: 99%